Effect of Shade and NPK Fertilizer on the Growth of Shorea assamica Dyer in the Nursery - Arif Irawan; Jafred E. Halawane (Jurnal Perbenihan Tanaman Hutan, 2016)
Shorea assamica Dyer is one of endangered species in the North Sulawesi. The species has high economic value, however information about technique of silviculture and its conservation are very limited. The research aims to determine the effect of shade and the use of NPK (15:15:15) fertilizer on growth rate of S.assamica in the nursery. The design was applied in this reserach according to randomized complete design with split plot design. The main plot was shade level and the sub plot was NPK fertilizer level. The treatments were covering four levels of NPK fertilizer (0; 0.25; 0.50 and 0.75 g/seedling) and three levels of shade (light, medium, and heavy). The results showed that the best combination of treatments for height and diameter growth, seedling dry weight, and seedling quality index of S. assamica on 6 months age was NPK fertilizer dosage of 0.5 g/seedling in moderate shade.